Duplicated membrane estrogen receptors in the European sea bass (Dicentrarchus labrax): Phylogeny, expression and regulation throughout the reproductive cycle. Issue 178 (April 2018) - Pinto, Patrícia I.S.; Andrade, André R.; Estêvão, M. Dulce; Alvarado, M. Victoria; Felip, Alicia; Power, Deborah M.
Highlights: Teleost genomes possess duplicate membrane estrogen receptors gpera and gperb . Sea bass gpera is mainly expressed in brain and pituitary in both sexes. Gperb has a more widespread tissue distribution. Both gpers are expressed in hypothalamus and pituitary along the reproductive cycle. Gpers showed differential seasonal and tissue regulation in both male and female. Abstract: The numerous estrogen functions reported across vertebrates have been classically explained by their binding to specific transcription factors, the nuclear estrogen receptors (ERs). Rapid non-genomic estrogenic responses have also been recently identified in vertebrates including fish, which can be mediated by membrane receptors such as the G protein-coupled estrogen receptor (Gper). In this study, two genes for Gper, namely gpera and gperb, were identified in the genome of a teleost fish, the European sea bass. Phylogenetic analysis indicated they were most likely retained after the 3R teleost-specific whole genome duplication and raises questions about their function in male and female sea bass. Gpera expression was mainly restricted to brain and pituitary in both sexes while gperb had a widespread tissue distribution with higher expression levels in gill filaments, kidney and head kidney. Both receptors were detected in the hypothalamus and pituitary of both sexes and significant changes in gpers expression were observed throughout the annual reproductive season. In female pituitaries, gpera showed an overall increase in expression throughout the reproductive season while gperb levels remained constant. In the hypothalamus, gpera had a higher expression during vitellogenesis and decreased in fish entering the ovary maturation and ovulation stage, while gperb expression increased at the final atresia stage. In males, gpers expression was constant in the hypothalamus and pituitary throughout the reproductive cycle apart from the mid- to late testicular development stage transition when a significant up-regulation of gpera occurred in the pituitary. The differential sex, seasonal and subtype-specific expression patterns detected for the two novel gper genes in sea bass suggests they may have acquired different and/or complementary roles in mediating estrogens actions in fish, namely on the neuroendocrine control of reproduction.